Analysis of Inhibiting Factors and Difficulties for Students in Writing Scientific Papers in Higher Education - Ihramsari Akidah; Muhajir (Journal for Lesson and Learning Studies, 2026)
In the 21st century, students' lack of knowledge in writing scientific papers. The urgency of researching factors that strengthen students' scientific writing skills. Therefore, the purpose of this study is to identify and analyse multidimensional factors that influence students' difficulties in scientific writing. The study used a mixed methods approach. The sample consisted of 150 Indonesian Literature and English students. Data collection techniques used questionnaires, semi-structured interviews, and documentation. Data analysis techniques used descriptive and inferential statistics with the help of SPSS version 29.0. The results showed a mean level of student difficulty of 3.57 (SD = 0.64) in the medium-high category. The KMO value = 0.871, Bartlett's χ² = 3254.231 (p < 0.001), and Cronbach's Alpha = 0.923 indicated excellent validity and reliability of the instrument. Regression analysis showed that lecturer guidance (β = 0.542) was the most dominant factor, followed by technical and cognitive aspects, while psychological aspects (β = -0.276) had a negative effect. In conclusion, students' scientific writing skills are determined by the synergy between academic guidance from lecturers, technical skills, and psychological support. Practical implications: Universities need writing skills training directly integrated with lecturer guidance.